Odpowiedź:
[tex]\begin{cases}3(2x-y)-2(x+4y)=6-10y\\0,5(x-3y)-(4y-x)=-8\end{cases}\\\\\\\begin{cases}6x-3y-2x-8y=6-10y\\0,5x-1,5y-4y+x=-8\end{cases}\\\\\\\begin{cases}4x-11y+10y=6\\1,5x-5,5y=-8\end{cases}\\\\\\\begin{cases}4x-y=6\\1,5x-5,5y=-8\end{cases}\\\\\\\begin{cases}-y=6-4x/\cdot(-1)\\1,5x-5,5y=-8\end{cases}\\\\\\\begin{cases}y=-6+4x\\1,5x-5,5y=-8\end{cases}[/tex]
[tex]1,5x-5,5(-6+4x)=-8\\\\1,5x+33-22x=-8\\\\-20,5x=-8-33\\\\-20,5x=-41\ \ /:(-20,5)\\\\x=2\\\\\\y=-6+4\cdot2=-6+8=2\\\\\begin{cases}x=2\\y=2\end{cases}[/tex]